ҚАРАҚАЛПАҚ ТИЛИНИҢ АРҚА ДИАЛЕКТИ КӘСИБИЙ ЛЕКСИКАСЫНЫҢ ҮЙРЕНИЛИЎ МӘСЕЛЕСИ - Кайпназарова, М.К. (FAN va JAMIYAT, 2018)
In the article there have been analyzed the professional words of the north dialects of the Karakalpak language. The peculiarities of using Karakalpak words in northern dialect, related to agriculture, cattle breeding and fishing industry are analyzed on the basis of concreate examples. Such studies, of course, are carried out by studying the native spoken language of the local population. Therefore, we realize that we should not be indifferent to the spoken language of the people.